2016
DOI: 10.3847/0004-637x/830/2/133
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin–helmholtz Instability in Solar Chromospheric Jets: Theory and Observation

Abstract: Using data obtained by the high-resolution CRisp Imaging SpectroPolarimeter instrument on the Swedish 1 m Solar Telescope, we investigate the dynamics and stability of quiet-Sun chromospheric jets observed at the disk center. Small-scale features, such as rapid redshifted and blueshifted excursions, appearing as high-speed jets in the wings of the Hα line, are characterized by short lifetimes and rapid fading without any descending behavior. To study the theoretical aspects of their stability without consideri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 78 publications
(125 reference statements)
2
39
1
Order By: Relevance
“…In practical terms, the Doppler shift of the K 3 (k 3 ) features provides an accurate velocity measure, one consistent across multiple lines. The spicule Article number, page 5 of 10 Doppler shifts that we measure from Ca ii K to be in the range 20 − 50 km s −1 confirm earlier spicule Doppler measurements from other spectral lines (Rouppe van der Voort et al 2009; Kuridze et al 2016), largely removing concern over statistics based on Hα differential profiles and reservations about the presence of such flows (Judge et al 2011). These Doppler measurements constitute the LOS component of the mass flow in spicules which, due to our top-down viewing angle, can be directly compared to the apparent spicule velocities, measured nearly perpendicularly to the limb, of up to 150 km s −1 (De Pontieu et al 2007;Pereira et al 2012Pereira et al , 2014Skogsrud et al 2015), if those apparent velocities were due to mass flows.…”
Section: Discussionsupporting
confidence: 86%
“…In practical terms, the Doppler shift of the K 3 (k 3 ) features provides an accurate velocity measure, one consistent across multiple lines. The spicule Article number, page 5 of 10 Doppler shifts that we measure from Ca ii K to be in the range 20 − 50 km s −1 confirm earlier spicule Doppler measurements from other spectral lines (Rouppe van der Voort et al 2009; Kuridze et al 2016), largely removing concern over statistics based on Hα differential profiles and reservations about the presence of such flows (Judge et al 2011). These Doppler measurements constitute the LOS component of the mass flow in spicules which, due to our top-down viewing angle, can be directly compared to the apparent spicule velocities, measured nearly perpendicularly to the limb, of up to 150 km s −1 (De Pontieu et al 2007;Pereira et al 2012Pereira et al , 2014Skogsrud et al 2015), if those apparent velocities were due to mass flows.…”
Section: Discussionsupporting
confidence: 86%
“…The MHD wave mode numbers at which we were able to calculate the instability characteristics at wavelengths comparable to the radius or width of the jet are between 10 and 65 and the KHI growth times at those wavelengths are of the order on a few minutes, generally in good agreement with the observations. It is curious to note that in searching KHI growth times of the order on few seconds, when studying the dynamics and stability of small-scale rapid redshifted and blueshifted excursions, appearing as high-speed jets in the wings of the Hα line, Kuridze et al (2016) had to assume the excitation of MHD waves with mode numbers up to 100. A typical property of the instability developing times, owing to the shape of the plotted dispersion curves, is that with increasing the examined wavelength the growth times become shorter-for instance, at λ KH = 10 Mm the KHI developing time in the coronal hole jet (Chen, Zhang, and Ma, 2012) is around 4.5 min, while at λ KH = 12 Mm it is equal to ∼ =2.1 min.…”
Section: Discussionmentioning
confidence: 99%
“…When observed on the limb, these are classified as Type I or Type II spicules (De Pontieu et al 2007b;Pereira et al 2012), and on disk they are identified as Rapid Blue/Red-Shifted Excursions (termed as RBE or RREs, Langangen et al 2008;Rouppe van der Voort et al 2009;Sekse et al 2013a,b;Kuridze et al 2015;Henriques et al 2016;Kuridze et al 2016, and references therein). Recently, both ground-and space-based observations have shown different types of waves and oscillations in these structures.…”
Section: Introductionmentioning
confidence: 99%